"Hamastan vs. Fatahland": A chance for progress in the Middle East? - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2007)
In mid-June 2007, the »Islamic Resistance Movement« Hamas gained the upper hand in the Gaza Strip after a series of bloody conflicts. After seizing control of security facilities, Hamas and announced the beginning of »Islamic rule« in the Strip. Palestinian President and Fatah leader, Mahmoud Abbas, responded by dissolving the government of national unity and declaring a state of emergency. He appointed an emergency government headed by Salam Fayyad, the previous minister of finance, declared the military wing of Hamas and its security forces to be illegal and ordered their disarmament. He has since rejected any cooperation with Hamas in unusually strong terms. Israel and the international community have regarded this split as an opportunity to resume support for the Palestinian Authority (PA) and return to the diplomatic process. (SWP Comments / SWP)
Keywords: 320